Using ex‐ante economic evaluation to inform research priorities in pesticide self‐poisoning prevention: the case of a shop‐based gatekeeper training programme in rural Sri Lanka. Issue 10 (12th August 2020) - Damerow, Sabine Margarete; Weerasinghe, Manjula; Madsen, Lizell Bustamante; Hansen, Kristian Schultz; Pearson, Melissa; Eddleston, Michael; Konradsen, Flemming
Abstract: Objectives: Suicide by pesticide self‐poisoning is a major public health challenge in low‐ and middle‐income countries. While effectiveness studies are required to test alternative prevention approaches, economic evidence is lacking to inform decision‐making in research priority setting. Therefore, this study aimed to estimate the costs of a shop‐based gatekeeper training programme for pesticide vendors seeking to prevent pesticide self‐poisoning in rural Sri Lanka and assess its potential for cost‐effectiveness. Methods: Ex‐ante cost and cost‐effectiveness threshold (CET) analyses were performed from a governmental perspective based on a three‐year analytic horizon, using 'no programme' as a comparator. A programme model targeting all 535 pesticide shops in the North Central Province and border areas was applied. Total programme costs (TPC) were estimated in 2019 USD using an ingredients approach and 3% annual discounting. The Sri Lankan gross domestic product per capita and life years saved were used as CET and effectiveness measure, respectively. Sensitivity analyses were performed. Results: TPC were estimated at 31 603.03 USD. TPC were sensitive to cost changes of training material and equipment and the programme lifetime. The programme needs to prevent an estimated 0.23 fatal pesticide self‐poisoning cases over three years to be considered cost‐effective. In the sensitivity analyses, the highest number of fatal cases needed to be prevented to obtain cost‐effectiveness was 4.55 over three years. Conclusions: From an economic perspective, the programme has a very high potential to be cost‐effective. Research assessing its effectiveness should therefore be completed, and research analysing its transferability to other settings prioritised. Abstract : Objectifs: Le suicide par auto‐intoxication par les pesticides est un défi majeur de santé publique dans les pays à revenu faible ou intermédiaire. Bien que des études d'efficacité soient nécessaires pour tester d'autres approches de prévention, les données économiques manquent pour informer la prise de décision dans les priorités de recherche. Par conséquent, cette étude visait à estimer les coûts d'un programme de formation des vendeurs dans les magasins de pesticides visant à prévenir l'auto‐intoxication par les pesticides dans les régions rurales du Sri Lanka et à évaluer son potentiel de rentabilité. Méthodes: Les analyses ex‐ante des coûts et des seuils de rentabilité (SR) ont été réalisées dans une perspective gouvernementale sur la base d'un horizon analytique de trois ans, en utilisant «l'absence de programme» comme comparateur. Un modèle de programme ciblant les 535 magasins de pesticides de la province du Centre‐Nord et des zones frontalières a été appliqué. Les coûts totaux du programme (CTP) ont été estimés en USD 2019 en utilisant une approche d'ingrédients et une remise annuelle de 3%. Le produit intérieur brut sri‐lankais par habitant et les années de vie sauvées ont été utilisés comme SR et mesure d'efficacité, respectivement. Des analyses de sensibilité ont été effectuées. Résultats: le CTP a été estimé à 31.603, 03 USD. Le CTP était sensible aux changements de coût du matériel et de l'équipement de formation et de la durée de vie du programme. Le programme devrait prévenir environ 0, 23 cas d'auto‐intoxication mortelle par des pesticide sur trois ans pour être considéré comme rentable. Dans les analyses de sensibilité, le plus grand nombre de cas mortels à prévenir pour obtenir une rentabilité était de 4, 55 sur trois ans. Conclusions: D'un point de vue économique, le programme a un potentiel très élevé pour être rentable. La recherche évaluant son efficacité doit donc être complétée et la recherche analysant sa transférabilité à d'autres contextes doit être priorisée.